A college degree recommendation model (2016)
Selecting a profession suitable to students` expectations implies taking into account multiple factors. Despite its usefulness and high impact, there are shortcomings in current university major recommendation models. Among these limitations are the lack of flexible models, the dependence on historical information and the inadequate weighting of the factors involved. In this paper, a new college degree recommendation model based on psychological student profiling and the analytical hierarchical process is presented. It includes database construction, student profiling, college degree information filtering and recommendation generation. Its implementation made it possible to improve reliability in the recommendation process of college degree. A case study is shown to demonstrate the model applicability.